Keberadaan Lie Detector dalam Pembuktian Tindak Pidana - Nida Aidatu (Jurnal Justice Aswaja, 2023)
This study aims to find and analyze criminal law in the regulation of lie detectors in court in proving criminal cases. The approach method in this study is normative, while the specification of this study is descriptive. The data used are secondary data consisting of primary legal materials in the form of laws and regulations such as the 1945 Constitution, Laws and secondary legal materials in the form of books, journals and writings related to the title of the study. The data analysis method is carried out qualitatively. Based on the study, it is concluded that in the concept of implementing criminal procedural law, material truth is obtained to obtain legal certainty. One way to achieve this is to ensure that the statements of the perpetrator or witness overlap and are not confusing/overlapping so that the lie detector can give his statement honestly. Provisions regarding the use of lie detectors in criminal trials do not yet have parameters that are expressly regulated in the Criminal Procedure Code, because lie detectors are not the main evidence in court, but rather the validity of the lie detector used in testimony. Crime. Legal cases require information from experts in forensic computer laboratories. The printout results were analyzed by a forensic psychologist who was an authorized expert in court, which constitutes additional evidence in the investigation file according to Article 184 paragraph 1 of the Criminal Procedure Code.